2018
DOI: 10.1016/j.rmed.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum 25-hydroxyvitamin D levels and pulmonary function, among Korean adults, during 2010–2014, by sex, age, and body mass index

Abstract: We found a significant association between serum 25(OH)D and pulmonary function, and this was related to sex, age and body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… 55 Increased odds of COPD development were reported in a cross-sectional analysis in smokers with a serum 25(OH)D concentration <50 nmol/L compared with smokers with a serum concentration ≥50 nmol/L. 56 Vitamin D deficiency was associated with decreased FEV 1 and FVC in the Korean population, 57 and in another study, researchers reported this association only in men without medical conditions, and not in women. 58 Furthermore, 6 cross-sectional 59–64 studies reported a positive association between serum 25(OH)D concentrations and FEV 1 in a general population, healthy individuals, and adolescents, but no longitudinal change in FEV 1 was observed in healthy individuals.…”
Section: Resultsmentioning
confidence: 97%
“… 55 Increased odds of COPD development were reported in a cross-sectional analysis in smokers with a serum 25(OH)D concentration <50 nmol/L compared with smokers with a serum concentration ≥50 nmol/L. 56 Vitamin D deficiency was associated with decreased FEV 1 and FVC in the Korean population, 57 and in another study, researchers reported this association only in men without medical conditions, and not in women. 58 Furthermore, 6 cross-sectional 59–64 studies reported a positive association between serum 25(OH)D concentrations and FEV 1 in a general population, healthy individuals, and adolescents, but no longitudinal change in FEV 1 was observed in healthy individuals.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, people whose family PIR was big than 1 had higher serum 25(OH)D concentration than people whose family PIR was less than 1. Moreover, serum vitamin D levels could also increase after sunlight and ultraviolet light exposure (34,35). Therefore, peoples sampled in summer months, exposed to more sunlight and ultraviolet light, had more vitamin D in serum compared to peoples in winter months.…”
Section: Demographic Population Characteristics Of 2609mentioning
confidence: 99%